(untitled) (PROCEEDING: The Annual International Conference on Islamic Education, 2018)
This research aims to; knowing the linearity of formal education of teachers and teaching experience on pedagogic mastery, this study population is madrasah teacher ibtidaiyah in MI Salafiyah Syafi’iyah Sooko District Kab. Mojokerto. Data collection techniques used questionnaires and documentation. Validity and Reliability Test The instrument in this study measures the content vibility by studying the instrument based on the literature, while the validity and reliability of the test instrument instrument by disseminating the instrument in a sample similar to the object of research after it is processed by the test is valid and reliable. There is a correlation between the linearity of formal teacher education and the teaching experience of pedagogical mastery in teaching (Spearman Correlataion). Models containing intercept are not suitable to be used in other words suitable model used is a model that contains the free variable (Final Model) according to table Model Fitting Information. The data used from the study are in accordance with the ordinal regression model used and this means that the model used is the most suitable model (Goodness-of-Fit). The result of Psudo R-Squere, this indicates that the variable Linearity of Formal Teacher Education and teaching experience can explain to pedagogic mastery or in other words the linearity of formal education of teacher and teaching experience influence to pedagogic mastery. With Estimates Parameter table, it can be explained that there is a tendency of linearity relationship of formal education of teacher and teaching experience to pedagogic mastery in teaching. From the results of the above test on the Test of Parallel Lines table, obtained ordinal model (proportional odds) gives a better data fit significantly compared with the general model.